A multivariate conditional model for streamflow prediction and spatial precipitation refinement - Liu, Zhiyong; Zhou, Ping; Chen, Xiuzhi; Guan, Yinghui (Journal of geophysical research. Atmospheres, 2015)
The effective prediction and estimation of hydrometeorological variables are important for water resources planning and management. In this study, we propose a multivariate conditional model for streamflow prediction and the refinement of spatial precipitation estimates. This model consists of high dimensional vine copulas, conditional bivariate copula simulations, and a quantile-copula function.
Gesehen am 29.06.2020